"I bled like you, brother, although I was a thousand miles away": postwar Yiddish sources on the experiences of Polish Jews in Soviet exile during World War II. Issue 1 (2nd January 2016) - Nesselrodt, Markus
ABSTRACT: An estimated 230, 000 Polish Jews escaped Nazi persecution during World War II by flight or deportation to the interior of the Soviet Union. This article examines early postwar Yiddish and Polish sources on their survival in Soviet exile such as poems, newspaper articles, and witness testimonies. Two sets of sources are analyzed in-depth, testimonies written by young people in Jewish Displaced Persons (DP) camps in occupied Germany and Yiddish poetry from Poland and the DP camps. The author argues that many former exiles were eager to write down their experiences. In doing so, they were aware of the complex nature of deportation and flight that characterized the experiences of Polish Jews in the Soviet Union. In their testimonies many young witnesses express their understanding that they too were "marked by the khurbn ." Whereas Yiddish poetry from the same period helps us understand how writers dealt with their own story of wartime survival outside the realm of German persecution. In their poetry they seek meaning in their own suffering and express their desire to establish a dialogue with other survivors.